Increased mitochondrial emission of reactive oxygen species and calpain activation are required for doxorubicin-induced cardiac and skeletal muscle myopathy - Min, Kisuk (J Physiol, 2015)
Although doxorubicin (DOX) is a highly effective anti-tumour agent used to treat a variety of cancers, DOX administration is associated with significant side effects, including myopathy of both cardiac and skeletal muscles. The mechanisms responsible for DOX-mediated myopathy remain a topic of debate. We tested the hypothesis that both increased mitochondrial reactive oxygen species (ROS) emission and activation of the cysteine protease calpain are required for DOX-induced myopathy in rat cardiac and skeletal muscle. Cause and effect was determined by administering a novel mitochondrial-targeted anti-oxidant to prevent DOX-induced increases in mitochondrial ROS emission, whereas a highly-selective pharmacological inhibitor was exploited to inhibit calpain activity. Our findings reveal that mitochondria are a major site of DOX-mediated ROS production in both cardiac and skeletal muscle fibres and the prevention of DOX-induced increases in mitochondrial ROS emission protects against fibre atrophy and contractile dysfunction in both cardiac and skeletal muscles. Furthermore, our results indicate that DOX-induced increases in mitochondrial ROS emission are required to activate calpain in heart and skeletal muscles and, importantly, calpain activation is a major contributor to DOX-induced myopathy. Taken together, these findings show that increased mitochondrial ROS production and calpain activation are significant contributors to the development of DOX-induced myopathy in both cardiac and skeletal muscle fibres.